The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1037/rep0000011
|View full text |Cite
|
Sign up to set email alerts
|

Work-related social skills: Definitions and interventions in public vocational rehabilitation.

Abstract: Public rehabilitation agency staff, constantly faced with addressing work related social skills, possess many insights about salient skills and interventions that can benefit future research and practice. Agencies currently address social skills deficits by providing interventions to both person and environment. The research provides directions for future research related to identification of social skills and interventions to address related deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Given the possible risk factors associated with unemployment and the inclusion of people with disabilities in formal work, for example, lack of job opportunities, low wages, prejudice regarding potentiality, and inadequate working conditions (Coutinho et al, 2017;Lorenzo & Silva, 2017;Tripney et al, 2017), there is evidence of the importance of the use of Social Skills Programs (SSPs) for the professional development of these individuals (Lindsay, Adams, McDougall, & Sanford, 2012;Phillips, Kaseroff, Fleming, & Huck, 2014;Soresi & Nota, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the possible risk factors associated with unemployment and the inclusion of people with disabilities in formal work, for example, lack of job opportunities, low wages, prejudice regarding potentiality, and inadequate working conditions (Coutinho et al, 2017;Lorenzo & Silva, 2017;Tripney et al, 2017), there is evidence of the importance of the use of Social Skills Programs (SSPs) for the professional development of these individuals (Lindsay, Adams, McDougall, & Sanford, 2012;Phillips, Kaseroff, Fleming, & Huck, 2014;Soresi & Nota, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Social skills can act as a protection factor for professional placement because they help people with physical disabilities deal with the demands of assertiveness (e.g., those related to the defense of their rights to accessibility and adaptation of workplaces) and expand friendships and social support links, which may increase opportunities for interaction and exposure to different professional contexts and activities (Murta & Guimarães, 2007;Wilson et al, 2006). Work-related SSPs have previously been tested with young people with and without disabilities and have shown that learning social skills contributes to more satisfactory performance in job interviews and in the activities of the role, especially in measures that have assessed initiative and the ability to interact with others in the workplace (Campos & Almeida, 2010;Donohue et al, 2005;Lindsay et al, 2012;Lopes, Gerolamo, Del Prette, Musetti, & Del Prette, 2015;Phillips et al, 2014;Soresi & Nota, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…27, nº 3, p. 677-692 -September/2019 professional performance by those working in the exact sciences. Regardless of the area of professional activity, however, at some time and to a greater or lesser extent, there needs to be some social interaction (Del Prette, Del Prette, & Correia, 1992) and therefore a good repertoire of social skills can be extremely important both for the individual's adaptation to higher education and subsequently for their entry into, and continuity in the labor market (Carter, Austin, & Trainor, 2012;Phillips, Kaseroff , Fleming, & Huck, 2014).…”
mentioning
confidence: 99%